Swinging between two poles. Henri Nouwen’s unique metaphor for spiritual transformation - G. Marchinkowski (Acta Theologica)
The article seeks to examine Henri Nouwen’s contribution to the study of spiritual transformation by uncovering his methodology, elucidating his sources, and exploring his central metaphor. When Nouwen considers the path to spiritual wholeness, he begins with an analysis of the typical Western lifestyle. Thereafter, he searches for an “antidote” to the sense of alienation he discovers. This “antidote” is expressed as a process of transformation into love. This article considers the nature of transformation in the classic mystical tradition and touches on the contributions of perennial philosophy and transpersonal psychology which may have influenced Nouwen. The question as to whether transformation is a linear, staged, or cyclical process is considered and Waaijman’s proposal that it should be described as a “way” is explored. Finally, the article contributes to the study of spiritual transformation by considering Nouwen’s description of transformation as a series of spiritual swings between poles.